Biosynthesis of Chiral Amino Alcohols via an Engineered Amine Dehydrogenase in E. coli - Tong, Feifei; Qin, Zongmin; Wang, Hongyue; Jiang, Yingying; Li, Junkuan; Ming, Hui; Qu, Ge; Xiao, Yazhong; Sun, Zhoutong (Frontiers in Bioengineering and Biotechnology, 2022)
Chiral amino alcohols are prevalent synthons in pharmaceuticals and synthetic bioactive compounds. Efficient synthesis of chiral amino alcohols using ammonia as the sole amino donor under mild conditions is highly desired and challenging in organic chemistry and biotechnology. Our previous work explored a panel of engineered amine dehydrogenases (AmDHs) derived from amino acid dehydrogenase (AADHs), enabling the one-step synthesis of chiral amino alcohols via the asymmetric reductive amination of α-hydroxy ketones. Although the AmDH-directed asymmetric reduction is in a high stereoselective manner, the activity is yet fully excavated. Herein, an engineered AmDH derived from a leucine dehydrogenase from Sporosarcina psychrophila (SpAmDH) was recruited as the starting enzyme, and the combinatorial active-site saturation test/iterative saturation mutagenesis (CAST/ISM) strategy was applied to improve the activity. After three rounds of mutagenesis in an iterative fashion, the best variant wh84 was obtained and proved to be effective in the asymmetric reductive amination of 1-hydroxy-2-butanone (1a) with 4-fold improvements in kcat/Km and total turnover number (TTN) values compared to those of the starting enzyme, while maintaining the high enantioselectivity (ee >99%) and thermostability (T5015 >53 oC). In preparative-scale reaction，the conversion of 100 mM and 200 mM 1a catalyzed by wh84 was up to 91-99%. Insight into the source of enhanced activity was gained by computational analysis. Our work expands the catalytic repertoire and toolbox of AmDHs.